2017
DOI: 10.4038/gmj.v22i2.7967
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed depression among older adults living in a semi urban community in Southern Sri Lanka

Abstract: Introduction: Depression is common in late life. Sri Lankan studies on depression in community living elderly are scarce. A sample of community living older people was assessed for presence of depressive symptoms. Methods:Randomly selected 300 people aged above 50 years from Bope-Poddala MOH area who were not diagnosed with neurological illness, major psychiatric illness and not having severe visual or hearing impairment were screened using Geriatric Depression Scale-Sinhala version (GDS-S). Medical records we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The association between gender and depression among older persons was inconsistent. Three studies showed no significant relationship [ 35 37 ], whereas Rajapakshe et al[ 38 ] found female gender as the strongest associated factor by multivariable analyses. Another study showed more complex gender-ethnicity interactions with depression, where only males in the ethnic minorities had increased odds of depression compared to males in the majority [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The association between gender and depression among older persons was inconsistent. Three studies showed no significant relationship [ 35 37 ], whereas Rajapakshe et al[ 38 ] found female gender as the strongest associated factor by multivariable analyses. Another study showed more complex gender-ethnicity interactions with depression, where only males in the ethnic minorities had increased odds of depression compared to males in the majority [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Association between gender and depression among older persons was inconsistent. Three studies showed no signi cant relationship [31][32][33], whereas Rajapakshe et al [34]found female gender as the strongest associated factor by multivariable analyses. Another study showed more complex gender-ethnicity interactions with depression where only males in the ethnic minorities had increased odds of depression compared to males in the majority [32].…”
Section: Older Personsmentioning
confidence: 90%